A Note on Sabos Custom in Hatay (Antioch) - San, Funda (BRILL ACADEMIC PUBLISHERS, 2017)
The paper describes a common custom, named sabos, practised almost in every district and village in Hatay (Antioch) and aimed primarily at collecting gold or money for the newlyweds. Though the effect of sabos has considerably decreased with time, it still continues to be widely practised in the area.
Keywords: Sabos; Wedding Ceremonies in Turkey; Turkish Lexicology; History